2018
DOI: 10.1017/s0967199418000084
|View full text |Cite
|
Sign up to set email alerts
|

Transition from blastomere to trophectoderm biopsy: comparing two preimplantation genetic testing for aneuploidies strategies

Abstract: SummaryShortly after the implementation of comprehensive chromosome screening (CCS) techniques for preimplantation genetic testing for aneuploidies (PGT-A), the discussion about the transition from day 3 to blastocyst stage biopsy was initiated. Trophectoderm biopsy with CCS is meant to overcome the limitations of cleavage-stage biopsy and single-cell analysis. The aim of this study was to assess the results obtained in our PGT-A programme after the implementation of this new strategy. Comparisons between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…More recently, cleavage-stage embryo biopsies have been largely replaced by trophectoderm (TE) biopsies. Blastocyst biopsy provides more cells and is performed at an embryonic stage more amenable to genetic analyses, and less sensitive to possible damage (Coll et al, 2018). We lack reports on the incidence of MZT after the use of ART in combination with PGT performed at the blastocyst stage.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, cleavage-stage embryo biopsies have been largely replaced by trophectoderm (TE) biopsies. Blastocyst biopsy provides more cells and is performed at an embryonic stage more amenable to genetic analyses, and less sensitive to possible damage (Coll et al, 2018). We lack reports on the incidence of MZT after the use of ART in combination with PGT performed at the blastocyst stage.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, transferred embryos in both groups were at blastocyst stage, however, bias remained since fresh ET was performed after CB but a frozen-warmed ET was administered after BB. No significant differences in implantation rate (50.3% fresh blastocyst transfer after CB vs. 61.4% FWBT after BB) and clinical pregnancy rate (56.1% vs. 65.3% in two groups respectively) were found between the two groups in the study (17).…”
Section: Discussionmentioning
confidence: 67%
“…However, the results were controversial. Some trials reported a more compromised implantation potential of biopsied embryos and an inferior clinical pregnancy rate per cycle after CB was performed (6,14,15), while others found no statistically significant differences between CB and BB (16,17). It is worth noting that bias may exist in previous studies e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Gamete manipulation, oocyte insemination, and embryo culture were performed according to standard protocols used in the IVF laboratory of the study's center [19].…”
Section: Embryo Manipulation and Pgt-amentioning
confidence: 99%